2014
DOI: 10.1590/1809-2950/446210114
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of gastrocnemius muscle stretching after contusion in rats

Abstract: | The aim of this study was to evaluate the acute effects of stretching after gastrocnemius contusion in rats. Thirty-three male Wistar rats were selected (8 weeks, 219±35 g) and divided into 4 groups: Control (CG, n=3) -intact; Lesion (LG, n=10); Stretching (SG, n=10): Lesion and Stretching (LSG, n=10). The right gastrocnemius (RG) was submitted to contusion. Stretching on RG was performed manually, with 4 repetitions of 30 seconds each day, for 5 consecutive days, beginning 72 hour after contusion. One week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…To our knowledge, only two studies have described the effect of stretching in injured muscle, which showed new myofibrils and also sarcomerogenesis after 14 days of performance of a stretching protocol 16,17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only two studies have described the effect of stretching in injured muscle, which showed new myofibrils and also sarcomerogenesis after 14 days of performance of a stretching protocol 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not yet known exactly how this therapy combination affect muscle repair 4,5,7,17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental animal models contribute to understanding the effects of lengthening stimulus, such as stretching, in the cellular mechanisms of skeletal muscle healing after contusion (Hwang et al, 2006;de Macedo et al, 2014de Macedo et al, , 2016. The involvement of desmin and laminin in force transmission has been described in the literature (De Deyne, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of desmin and laminin in force transmission has been described in the literature (De Deyne, 2001). An increase in sarcomerogenesis and an antifibrotic effect after a stretching protocol of injured rat gastrocnemius has been reported (de Macedo et al, 2014(de Macedo et al, , 2016. Although the proteins desmin and laminin involved in the sarcomerogenesis and muscle healing, have not yet been investigated (Yu & Thornell, 2002;Cação-Benedini et al;Gianelo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%